HIV and penetrating abdominal trauma: does HIV influence the outcome? - McPherson, Deidre Estelle Kathleen (Department of Surgery, 2018)
Background: Human immunodeficiency virus (HIV) infection and trauma are significant contributors to the burden of disease in South Africa. There is an increase in prevalence of HIV sero-positivity in trauma patients. However, there are conflicting reports about the influence of HIV in outcomes after trauma or surgery. Although HIV and the acquired immunodeficiency syndrome (AIDS) can potentially affect outcomes, there have been few studies comparing trauma outcomes in HIV positive versus HIV negative patients. To the best of our knowledge, there have been no studies to date that have compared HIV positive and HIV negative patients with penetrating (gunshot or stab) abdominal wounds requiring an explorative laparotomy. The purpose of this study was to determine whether the outcome of hemodynamically stable patients undergoing explorative laparotomy for penetrating abdominal trauma differed in HIV positive patients versus HIV negative patients. Methods: This was an observational prospective study over a 16-month period from February 2016 to May 2017. All hemodynamically stable patients with penetrating abdominal trauma requiring a laparotomy were included in the study. To evaluate the impact of HIV on outcome, the mechanism of injury, the HIV-status, age, the penetrating abdominal trauma index (PATI), and the revised trauma score (RTS) were entered into a binary logistic regression model. Outcome parameters were in-hospital death, morbidity (defined as one or more distinct complications) during hospitalization was graded as per Clavien-Dindo classification of complications, admission to intensive care unit (ICU), relaparotomy within 30 days, and length of stay longer than 30 days. Variables were sought in bivariate analysis. Results: A total of 209 patients, 94% male, with a mean age of 29 ± 10 years were analysed. Twenty-eight patients (13%) were HIV positive. The mean CD4 count in the HIV positive group was 401 ± 254. The two groups were comparable except for race; 79% were black in the HIV positive group vs. 41% in the HIV negative group. All patients underwent explorative laparotomy of which 10 (4.8%) laparotomies were negative. There were two (0.96%) deaths, both in HIV negative group. The complication rate was 34% (n=72). There was no association between CD4 count and complications (p=0.234). Twenty-nine patients (14%) were admitted to the ICU. A higher PATI, advancing age, and a lower RTS were significant risk factors for worsened outcome. After 30 days, 12 patients (5.7%) were still in hospital. PATI was the single independent predictor in multivariate analysis. Twenty-four patients (11%) underwent a second laparotomy and the PATI was again the only significant predictor of outcome. Conclusion: The incidence of HIV in our cohort is 13%, which is similar to the reported incidence of HIV in the Western Cape of 15%. There were no significant baseline differences between the HIV positive and negative groups. Our results further showed that HIV status was not an independent predictor for morbidity, admission to ICU, relaparotomy, prolonged hospital stay or mortality. The patient's HIV status does not influence their outcomes in penetrating abdominal trauma.